Chatbots and Communication: The Growing Role of Artificial Intelligence in Addressing and Shaping Customer Needs - Lee, Sae Bom (Business Communication Research and Practice, 2020)
Objectives:This study examines the advantages of introducing chatbots and the different kinds of chatbot services in the e-commerce industry that are operating abroad. It also seeks to determine changes in future communication with companies and customers. Methods:The main characteristics of e-commerce chatbots will be explored through four examples: the chatbots used by 1-800-Flowers, Sephora, PVR Cinemas, and Vainu. Results:Sephora provides personalized services such as information delivery and recommendations through chatbots. 1-800-Flowers provides useful information to customers through interactive commerce services, as well as voice orders through Alexa for a convenient purchasing experience. PVR Cinemas supports purchasing and reservation functions to quickly solve customer problems, while Vainu has demonstrated that it can acquire customer information and use it for marketing by asking various questions to customers. Through these four cases, this study confirmed that product search, upselling, and marketing functions are the main advantages that can be obtained through communication with customers through chatbots in e-commerce transactions. Conclusions:It was confirmed that chatbots contribute to improving the productivity and efficiency of existing business operations, and in particular, improving the convenience of customers’ shopping, ordering, and payment experiences. In addition, as companies attempt to provide new shopping experiences to customers using chatbots, communication with customers through chatbots in the e-commerce field is expected to increase in the future. KCI Citation Count: 1